Let the given statement be P(n), as
First, we check if it is true for n = 1,
∴ It is true for n = 1.
Now we assume that it is true for some positive integer k, such that
We shall prove that P(k + 1)is true,
Solving the left hand side with n = k + 1
[From equation (1)]
Which is equal to the Right hand side for n = k + 1.We proved that P(k + 1) is true.
Hence by principle of mathematical induction it is true for all n ∈ N.
Rate this question :
Prove that cos αRD Sharma - Mathematics
Prove that sin xRD Sharma - Mathematics
Prove that <spanRD Sharma - Mathematics